Cold Atmospheric Plasma (CAP) Changes Gene Expression of Key Molecules of the Wound Healing Machinery and Improves Wound Healing In Vitro and In Vivo - Stephanie Arndt; Petra Unger; Eva Wacker; Tetsuji Shimizu; J. Heinlin; Yangfang Li; Hubertus M. Thomas; Gregor E. Morfill; Julia Zimmermann; Anja‐Katrin Bosserhoff; Sigrid Karrer (2013)
Cold atmospheric plasma (CAP) has the potential to interact with tissue or cells leading to fast, painless and efficient disinfection and furthermore has positive effects on wound healing and tissue regeneration. For clinical implementation it is necessary to examine how CAP improves wound healing and which molecular changes occur after the CAP treatment. In the present study we used the second generation MicroPlaSter ß® in analogy to the current clinical standard (2 min treatment time) in order to determine molecular changes induced by CAP using in vitro cell culture studies with human fibroblasts and an in vivo mouse skin wound healing model. Our in vitro analysis revealed that the CAP treatment induces the expression of important key genes crucial for the wound healing response like IL-6, IL-8, MCP-1, TGF-ß1, TGF-ß2, and promotes the production of collagen type I and alpha-SMA. Scratch wound healing assays showed improved cell migration, whereas cell proliferation analyzed by XTT method, and the apoptotic machinery analyzed by protein array technology, was not altered by CAP in dermal fibroblasts. An in vivo wound healing model confirmed that the CAP treatment affects above mentioned genes involved in wound healing, tissue injury and repair. Additionally, we observed that the CAP treatment improves wound healing in mice, no relevant side effects were detected. We suggest that improved wound healing might be due to the activation of a specified panel of cytokines and growth factors by CAP. In summary, our in vitro human and in vivo animal data suggest that the 2 min treatment with the MicroPlaSter ß® is an effective technique for activating wound healing relevant molecules in dermal fibroblasts leading to improved wound healing, whereas the mechanisms which contribute to these observed effects have to be further investigated.